Question
upstudy study bank question image url

\[ P(x)=x^{3}+2 x^{2}-6 x-4, \quad c=2 \] Evaluate \( D(x) \) for the given value of c, (Simplify your answers completely,) \[ \begin{aligned} P(2) & =(2)^{3}+2(\square)-6(2)-4 \\ & =8+2(\square)-6(2)-4 \\ & =8+(\square)=12-4 \\ & =\square \square \square) \end{aligned} \] Since? \( \square \) is 3 zero of \( P(x), x=2 \) \( \square \) is a factor of \( P(x) \),

Ask by Rodriguez Warren. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( P(2) = 0 \) and \( D(x) = x² + 4x + 2 \).

Solution

We are given   P(x) = x³ + 2x² – 6x – 4      and  c = 2. Step 1. Evaluate P(2):   P(2) = (2)³ + 2(2)² – 6(2) – 4      = 8 + 2(4) – 12 – 4      = 8 + 8 – 12 – 4      = 0 Thus, P(2) = 0. Step 2. Since P(2)=0, by the Factor Theorem, x = 2 is a zero of P(x) and (x – 2) is a factor. Step 3. To find D(x) (also called the depressed polynomial), perform synthetic division of P(x) by x – 2. Set up synthetic division using the coefficients of P(x):   Coefficients: 1  2  –6  –4   c = 2     Bring down the 1.     Multiply 1 by 2 -> 2. Add to 2 -> 4.     Multiply 4 by 2 -> 8. Add to –6 -> 2.     Multiply 2 by 2 -> 4. Add to –4 -> 0. The synthetic division steps:     2 |  1   2  –6  –4         2   4   2      –––––––––––––––       1   4   2   0 The quotient (depressed polynomial) is given by the coefficients 1, 4, and 2, which corresponds to:   D(x) = x² + 4x + 2 Summary of Fill-in-the-Blanks:   P(2) = (2)³ + 2(2)² – 6(2) – 4       = 8 + 2(4) – 6(2) – 4       = 8 + 8 – 12 – 4       = 0 Thus, since 0 was obtained, x = 2 is a zero of P(x) and hence (x – 2) is a factor. Final Answers:   P(2) = 0,   D(x) = x² + 4x + 2.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

First, let's evaluate \( P(2) \). Substituting \( c = 2 \) into your polynomial, we get: \[ P(2) = (2)^3 + 2(2)^2 - 6(2) - 4 = 8 + 8 - 12 - 4 = 0. \] This means that \( P(2) = 0 \)! Thus, \( (x - 2) \) is indeed a factor of \( P(x) \). Now, depending on how you like to express \( P(x) \), you can perform polynomial long division or synthetic division to factor \( P(x) \) as follows: Since \( P(x) = (x - 2)(\text{Quadratic}) \), you can find the other factor by dividing \( P(x) \) by \( (x - 2) \). When you do this, you'll find that \( P(x) \) can be factored into \( P(x) = (x - 2)(x^2 + 4x + 2) \). Let's get solving!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy